Draft Annual Plan 1983-84 Volume VI General Areas Government of Assam - Planning Commission (Planning Commission, 1983)
The academic activities will be confined to the University College and other institutional campus as well as to the demonstrative and exceptional activities conducted by various voluntary organisations, groups and individuals, on scientific advancement and technology developments. For the purpose of environmental protection also both academic and field activities are being carried on under the plan programmes and their extension to the educational institutions as well as to the areas not already covered has been proposed in the instant schemes.
Government of Assam, Planning and Development Department